Post-industrial urban areas in the context of ruination, demolition and urban regeneration in a post-socialist city: experiences of Lódz, Poland - Kazimierczak,Jaroslaw (2018)
Since the beginning of the 1990s Lódz has become one of the largest and the fastest shrinking cities in Poland and Central-Eastern Europe. This is the result of political transformation in Poland at the turn of the 1980s and 1990s, which caused the collapse of Lódz economy based on textile industry monoculture. The radical population change has triggered highly dynamic transformations in the urban fabric of Lódz and produced numerous ruins, voidances, unused houses and dwellings, abandoned and vacant land in a contemporary city, especially in its central, historical districts. Furthermore, one of the key roles in the process of ruination of Lódzs 19th-century urban tissue was played by the communists who ruled the city without any respect to its urban heritage for almost 50 years from the end of World War II. That was an intentional and ideologically motivated policy. In contrast, new capitalist circumstances of urban development in Poland since political and economic transformation in 1989 have freed private property developers game of urban space that has strengthened urban sprawl and decapitalization of historical, especially post-industrial buildings in Lódz downtown. The aim of our research is to identify qualities of post-industrial urban areas in the downtown of Lódz in the period of 1989-2016 and then the role of ruined and abandoned post-industrial buildings in the urban regeneration process.